Cumulative plasma HIV burden disparities among adults in HIV care: implications for HIV transmission in the era of treatment as prevention. (24th August 2018) - Hughes, Alison J.; Rector, Amadeia; Jimenez, Veronica; Brock, Jon; Scheer, Susan
Abstract : Objective: To characterize disparities in cumulative plasma HIV burden in a sample of adults accessing HIV care in San Francisco, California. Design: Observational cohort and supplemental HIV surveillance data. Methods: Data from the San Francisco Medical Monitoring Project 2012–2014 cycles and HIV surveillance data were used to create an analytic cohort followed for 2 years. Matched HIV viral load test results from HIV surveillance were used to create five viral outcome measures: any unsuppressed viral load (>200 copies/ml), any transmittable viral load (>1500 copies/ml), person-time spent unsuppressed, person-time spent transmittable, and 2-year viremia copy-years, a measure of cumulative plasma HIV burden. Rao-Scott chi-squares and analysis of variance examined differences in durable suppression and mean percentage time spent unsuppressed and transmittable. Weighted linear regression was used to describe differences in cumulative HIV burden. Results: Adults receiving HIV care spent approximately 12% of the 2-year time period with an unsuppressed viral load and approximately 7% of the time at a transmittable viral level. Factors independently associated with higher cumulative HIV viremia in an adjusted model included trans women identity, younger age, lower CD4 + cell count, and a history of homelessness, incarceration, not taking ART, and nonadherence to ART. Conclusion: Although 95% of the cohort of adults in HIV care in San Francisco self-reported ART use during MMP interview, they spent on average almost 1 month per year at a transmittable viral level. We identified characteristics of those who were more likely to have higher viral burden, highlighting priorities for resource allocation to reduce onward HIV transmission.